2021
DOI: 10.1007/s10098-021-02165-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic efficiency of resource recovery—analysis of time-dependent changes on sustainability perception of waste management scenarios

Abstract: Waste management systems are modelled to provide a public waste management service and need to be able to meet environmental sustainability requirements at a cost that is acceptable to system users/citizens. Overall environmental, economic, and/or socio-economic sustainability of waste management in previous publications is done through independent analyses and comparisons of obtained results or through multicriterial ranking of different alternatives where final results do not have a meaningful physical signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…37,38 In addition, effective waste management can bring significant economic benefits. 39,40 Therefore, there is an urgent need to study the migration and transition of bromides during the coupled pyrolysis of various additives and WPCBs. Some review articles currently summarize and look forward to precious metal recovery, 41,42 recycling methods, 43,44 recycling policy, 45,46 and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…37,38 In addition, effective waste management can bring significant economic benefits. 39,40 Therefore, there is an urgent need to study the migration and transition of bromides during the coupled pyrolysis of various additives and WPCBs. Some review articles currently summarize and look forward to precious metal recovery, 41,42 recycling methods, 43,44 recycling policy, 45,46 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many scholars have studied the effect of additives on the pyrolysis of WPCBs recently and found that additives can enhance pyrolysis oils’ quality and fix pyrolytic halogens effectively . Recovery of low-bromine and light pyrolysis oils from WPCBs is crucial to carbon reduction since these oils can be used as fuels. , In addition, effective waste management can bring significant economic benefits. , Therefore, there is an urgent need to study the migration and transition of bromides during the coupled pyrolysis of various additives and WPCBs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly is done in (Westerhout et al 1998) and (Larrain et al 2020) for the average composition of mixed plastic waste, where in (Westerhout et al 1998) differences between three different processes are also analyzed. In (Tomić et al 2022a) economic indices of thermochemical conversion technologies are compared with results for other technologies. In these publications literature review data are used for system and economy modeling.…”
Section: Introductionmentioning
confidence: 99%